2016
DOI: 10.1038/ncomms12235
|View full text |Cite
|
Sign up to set email alerts
|

SIRT7 is a histone desuccinylase that functionally links to chromatin compaction and genome stability

Abstract: Although SIRT7 is a member of sirtuin family proteins that are described as NAD+-dependent class III histone deacetylases, the intrinsic enzymatic activity of this sirtuin protein remains to be investigated and the cellular function of SIRT7 remains to be explored. Here we report that SIRT7 is an NAD+-dependent histone desuccinylase. We show that SIRT7 is recruited to DNA double-strand breaks (DSBs) in a PARP1-dependent manner and catalyses desuccinylation of H3K122 therein, thereby promoting chromatin condens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
295
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 289 publications
(305 citation statements)
references
References 69 publications
9
295
0
1
Order By: Relevance
“…γH2AX is an important marker for DNA damage response. In previous publication (Li et al, 2016), the authors observed different DNA damage response in different cell lines. In MCF7 cells, depletion of SIRT7 significantly enhanced γH2AX level.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…γH2AX is an important marker for DNA damage response. In previous publication (Li et al, 2016), the authors observed different DNA damage response in different cell lines. In MCF7 cells, depletion of SIRT7 significantly enhanced γH2AX level.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, SIRT7 is also shown to be an activator that stimulates ribosomal biogenesis in dividing cells (Tsai et al, 2014) by activating rDNA transcription through multiple mechanisms (Chen et al, 2016; Ford et al, 2006; Tsai et al, 2012), thereby supporting the high biosynthetic and metabolic demands of cancer cells. Recent studies also show that SIRT7 can modulate DNA repair and maintain genome integrity (Li et al, 2016; Vazquez et al, 2016). In addition to its role in cancer, SIRT7 also plays an important role in the regulation of cell death and damage by inhibiting p53, Ras, and Akt signaling pathways in the heart (Vakhrusheva et al, 2008a; Vakhrusheva et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…The recent identification of a direct role for SIRT7 in the DSB repair of the NHEJ pathway established a functional link between SIRT7-mediated H3K18 deacetylation and 53BP1 recruitment to sites of DNA damage 26. Interestingly, SIRT7 overexpression increased both NHEJ and HR repair efficiency in reporter cell lines 17, 22. Although we did not determine whether SIRT7 affects the NHEJ or HR repair pathways, we provide clear evidence that 5-FU induced SIRT7 degradation is involved in increased radiosensitivity in colorectal cancer cell lines and immune-compromised mice.…”
Section: Discussionmentioning
confidence: 99%
“…In these assay conditions, SIRT7 did not exhibit any measurable activity, likely due to its preference for nucleosomal histones over peptide substrates 50 . Using cell-based proteomics methods, SIRT7 was characterized as a histone desuccinylase with function in the DNA damage response 51 . Another study demonstrated that SIRT3 has decrotonylase activity in vitro and that knockdown of SIRT3 increased histone Kcr levels, which correlated with increases in gene expression 52 .…”
Section: Writers and Erasers Of Lys Acylationmentioning
confidence: 99%